First results of a randomized clinical trial of fast neutrons compared with X or gamma rays in treatment of advanced tumours of the head and neck. Report to the Medical Research Council. Issue 5972 (21st June 1975) - Catterall, M; Sutherland, I; Bewley, D K
Abstract : Results of the first randomized clinical trial to compare the effects of fast neutrons and those of x or gamma rays (photons) in treating patients with advanced tumours of the head and neck are reported. In 37 out of 52 patients treated with neutrons and 16 out of 50 treated with photons the local tumour completely regressed; the tumour later recurred in nine of the 16 photon patients but in none of the 37 neutron patients. The advantages to the neutron-treated patients were seen in tumours of well and poorly differentiated histology and in each site. Complications after treatment did not differ significantly between the groups. Despite these substantial differences in local control of the tumour there were no significant differences in mortality between the series. A detailed study of the effective doses and the response of tumours and normal tissue in each series indicated that the improved results from neutron therapy were due to differences in the biological quality of the beam and not to the rather higher average effective dose in the neutron series. To assess the long-term effects of neutron treatment patients in earlier stages of disease and with smaller tumours should be included in the next phase of the trial.